Lactate-mediated metabolic reprogramming of tumor-associated macrophages: implications for tumor progression and therapeutic potential - Jin, Xiaohan; Zhang, Ni; Yan, Tinghao; Wei, Jingyang; Hao, Lingli; Sun, Changgang; Zhao, Haibo; Jiang, Shulong (Frontiers in Immunology, 2025)
The tumor microenvironment (TME) is characterized by distinct metabolic adaptations that not only drive tumor progression but also profoundly influence immune responses. Among these adaptations, lactate, a key metabolic byproduct of aerobic glycolysis, accumulates in the TME and plays a pivotal role in regulating cellular metabolism and immune cell function. Tumor-associated macrophages (TAMs), known for their remarkable functional plasticity, serve as critical regulators of the immune microenvironment and tumor progression. Lactate modulates TAM polarization by influencing the M1/M2 phenotypic balance through diverse signaling pathways, while simultaneously driving metabolic reprogramming. Furthermore, lactate-mediated histone and protein lactylation reshapes TAM gene expression, reinforcing their immunosuppressive properties. From a therapeutic perspective, targeting lactate metabolism has shown promise in reprogramming TAMs and enhancing anti-tumor immunity. Combining these metabolic interventions with immunotherapies may further augment treatment efficacy. This review underscores the crucial role of lactate in TAM regulation and tumor progression, highlighting its potential as a promising therapeutic target in cancer treatment.